Analisis Pertandingan Tim Perseden Denpasar Pada Kompetisi Liga 3 PSSI Bali 2021 - Muhamad Fauzi; Syarif Hidayat; Luh Putu Tuti Ariani (Jurnal Penelitian Mahasiswa Indonesia, 2023)
One of the goals of every football team is to score more goals against the opponent than the goal. This study aims to analyze the shooting and scoring patterns of the Denpasar Perseden team during the 2021 PSSI Bali League 3. The research method used in this study is descriptive quantitative by observing all Denpasar Perseden matches during Liga 3 PSSI Bali 2021 (8 matches), which will produce time intervals (15 minutes), type of play, number of passes before the occurrence of shoting and scoring, player actions before shooting and scoring, player positions in playing and playing zones. Based on the results of data processing and analysis, based on the time interval (15 minutes) the best shooting occurs in minutes 31-45 (+A.T) or as much as 20% and the best scoring occurs in minutes 16-30 or as much as 25%. From the type of play such as open play and set play, it is also calculated the number of shooting and scoring that has been successfully made by Perseden Denpasar. When open play is created 29 times (86%) shooting, and when set play is created 21 times (14%) shooting. The number of scoring is 19 (79%) during open play, and 5 (21%) from set play situations. Based on passing before shooting, the best shooting percentage of Denpasar Perseden occurs in three times (3 passes) passing before shooting as much as 22 times shooting or 15% of the total shooting, while the best scoring percentage of Denpasar Perseden occurs four times (4 passing) and eight times (8 passing) passing before scoring 4 times or 16% of the total scoring. Then at the beginning / action before shooting, the best shooting percentage of Denpasar Perseden occurs in Control + Shoot as much as 62 or 41% of the total shooting, while the best scoring percentage of Denpasar Perseden best Control + Dribble + Shoot is 9 or 37% of the total scoring. From the position of players, the winger is the most in shooting 51 times (34%) and the most scoring is created by the winger, namely 12 goals (50%). Then in the best zone of shooting occurs Central Advenced 51 times or 34% shooting and the most scoring occurs Central Ultra Offensive, which is 11 times or 45%. This data has implications for the evaluation of the tactical training program and also on one of the guidelines in compiling the Denpasar Perseden training program for the next competition